ANALISIS PENGARUH PROMOSI, BRAND AWARENESS, CITRA DESTINASI TERHADAP KEPUASAN BERKUNJUNG WISATAWAN DI SITU GINTUNG PARK DAN BSD OCEAN PARK KOTA TANGERANG SELATAN - Verry Cyasmoro (Eduturisma, 2020)
This study aims to know the influence of Promotion , brand Awarenees , destination image variable on tourist satisfaction at Situ gintung Park and BSD Ocean Park, South Tangerang City, Banten. This research uses quantitative approach with research. The collection of data obtained through a questionnaire distributed to 100 respondents. The sampling technique of this research using purposive sampling and the respondent is domestic tourist who come from situ Gintung Park and BSD Ocean Park outside , at least twice visited to the attraction in Soauth Tangerang City for tour,The data analysis in this research use quantitatif analysis. The results showed that: promotion variable significantly influence positif tourist satisfaction, the destination image variable significantly influence positif tourist Statisfaction variable, and tourist satisfaction variable significantly influence positif tourist Brand awareness Simultaneosly